Mechanism and application of full-anchor cable support mechanism for direct roof with thick soft rock in mining roadway - LI Yongchao; WANG Yin; LUO Gang; ZHANG Yangqiang (矿业科学学报, 2025)
Due to the small anchoring range and low support strength of anchor rod support for thick soft rock roof, it can lead to severe deformation and even instability and failure of surrounding rock. Through rock mechanics experiments, the irrationality of using thick soft rock as an anchoring layer was elucidated, and the rationality and supporting mechanism of full anchor support were established. The supporting effect of full anchor support was verified through numerical simulation, and the supporting method was optimized. The research results indicate that thick soft rock has low strength and is prone to deformation, making it unsuitable as the main anchoring layer; Due to the small range of anchor support, anchor support and anchor cable combined support are not suitable for thick soft rock environments; The combined support of long and short anchor cables strengthens the shallow surrounding rock, and its support effect is better than the previous two. The full anchor cable support of equal length can anchor all thick soft rocks in the deep stable rock layer through methods such as homogenization stress and strengthened anchoring, and its support effect is better than that of anchor cable combined support. On site applications have shown that by adjusting key parameters such as anchor cable length and spacing, combined with economic principles, the optimized support scheme can reduce the plastic zone of the roof, increase the working resistance of the anchor cable, reduce the deformation of the surrounding rock of the roadway, and achieve good support effects with deformation rates of 3.68 % and 3.13 % for the roof and two sides, respectively.